Therapeutic Targeting of Hepatic Macrophages for the Treatment of Liver Diseases - van der Heide, Daphne; Weiskirchen, Ralf; Bansal, Ruchi (Frontiers in Immunology, 2019)
Hepatic macrophages play a central role in maintaining homeostasis in the liver, as well as in the initiation and progression of liver diseases. Hepatic macrophages can mainly derive from resident hepatic macrophages called Kupffer cells or circulating bone marrow-derived monocytes. Kupffer cells are self-renewing and typically non-migrating macrophages in the liver and are stationed in the sinusoids of the liver in contrast to macrophages originating from circulating monocytes. Kupffer cells regulate liver homeostasis by mediating immunity against non-pathogenic blood-borne molecules, while participating in coordinated immune responses leading to pathogen clearance, leukocyte recruitment and antigen presentation to lymphocytes present in the vasculature. Monocyte-derived macrophages infiltrate into the liver tissue when metabolic or toxic damage instigates and are likely dispensable for replenishing the macrophage population in homeostasis. In recent years, different populations of hepatic macrophages have been identified with distinct phenotypes with discrete functions, far beyond the central dogma of M1 and M2 macrophages. Hepatic macrophages play a central role in the pathogenesis of acute and chronic liver failure, liver fibrosis, non-alcoholic fatty liver disease, alcoholic liver disease, viral hepatitis, and hepatocellular carcinoma, as well as in disease resolution. The understanding of the role of hepatic macrophages in liver diseases provides opportunities for the development of targeted therapeutics for respective malignancies. This review will summarize the current knowledge of the hepatic macrophages, their origin, functions, their critical role in maintaining homeostasis and in the progression or resolution of liver diseases. Furthermore, we will provide a comprehensive overview of the therapeutic targeting strategies against hepatic macrophages developed for the treatment of liver diseases.